Selective isolation of actinomycetes from mangrove forest of Pahang, Malaysia - Abdul Malek, Nurfathiah; Chowdhury, Ahmed Jalal Khan; Zainuddin, Zarina; Zainal Abidin, Zaima Azira (2014)
Actinomycetes are widely distributed in nature and are important industrially and pharmaceutically. They are renowned for their unique capabilities to produce biologically active metabolites. Poorly studied marine ecosystem, particularly mangrove offers a promising natural resource of new actinomycetes due to their high species diversity and novel biosynthetic capabilities. This study aims to assess the diversity of actinomycetes from mangrove forest of Pahang, Malaysia. Various selective isolation media and pre-treatments were employed for maximum isolation of mangrove actinomycetes. Sediment samples were collected from seven stations and air dried prior isolation. The samples were then pre-treated using wet heat and dry heat method followed by dilution plating on 8 media – starch-yeast extract, yeast extract-malt extract agar, oatmeal agar, inorganic salt-starch agar, starch casein agar, glucose asparagine agar, actinomycete isolation agar and marine agar. A total of 4850 actinomycete isolates had been successfully recovered. It was observed that inorganic-salt starch agar (ISP4) displayed the highest percentage of actinomycetes recovery (31.7 %), followed by actinomycete isolation agar (AIA) (24.1 %). Starch-yeast extract (SYE) and starch casein agar (SCA) were found to be more efficient in isolating wide variety of actinomycetes based on their morphological appearance. Moreover, both SYE and SCA were found to be more suitable for the isolation of non-Streptomyces isolates. Besides that, it was observed that wet heat pre-treatment was more effective in isolating mangrove actinomycetes as 81.4 % of total isolates were yielded using this moist-heating technique. On the other hand, dry eat treatment was better in the enumeration of spore-forming actinomycetes and removal of unwanted microorganisms, despite the lower number of isolates recovered. Of both pre-treatments, station 1 which is located within the deep mangrove forest area farthest from the coastal line recorded the highest recovery of actinomycetes (23.7 %), with Streptomyces and Micromonospora-like isolates being the most predominant observed from all sampling sites. The presence of relatively large number of isolates suggests that Pahang mangrove forest is a potentially rich source of actinomycetes.